IMPOLITENESS STRATEGIES USED BY MALE AND FEMALE STUDENTS IN CLASSROOM INTERACTION - Ersika Puspita Dani (Jurnal Mantik Penusa, 2017)
A campus is the setting where politeness is educated and where the relationship between lecturers and students, and students to students should be well established. This case could lead to the development of society which is moving to a more advanced and modern one. Nowadays, there seems to be a disruption in classroom interaction where impolite utterances are more likely to be used. Based on researcher’s observation, there is a new awkwardness that female more produced the impolite utterances than male. This phenomenon can be found in daily classroom interaction where students perform impolite speech events. The objectives of the study was to find out the types of impoliteness strategies used by male and female students in classroom interaction. The study was descriptive qualitative. The subject of the study was class TI V Regular Sore of STMIK Pelita Nusantara which had been chosen randomly. The data of the study is the impolite utterances of transcripts which is recorded from the conversation in the classroom interaction. The data were identified, analyzed and categorized based on Culpeper’s (1996, 2003), Bousfield’s (2007), and Beebe’s (1995) theory. The findings of the study showed that there were five types of impoliteness strategy found in both data of male and female students, namely: bald on record impoliteness, positive impoliteness, negative impoliteness, sarcasm or mock politeness, and withhold politeness. Commonly male students is the more frequent produced impolite utterances than female students did. Based on the findings, it can be concluded that overall male and female students had equal chance to perform impoliteness in classroom interaction. Some suggestions are directed to those who are interested in understanding impoliteness strategy as found in practice.  Keywords: impoliteness strategies, male and female student, classroom interaction